2017
DOI: 10.1177/0954008317744869
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of novel soluble polyarylates derived from 9,9-bis[4-(4-chloroformylphenoxy)phenyl]xanthene with various bisphenols

Abstract: A series of new polyarylates bearing cardo xanthene groups were synthesized by phase-transfer-catalyzed interfacial polycondensation of 9,9-bis[4-(4-chloroformylphenoxy)phenyl]xanthene with various bisphenols containing the isopropylidene, hexafluoroisopropylidene, 1-phenylethylidene, diphenylmethane, cyclohexane, and xanthene structures. High-molecular-weight polyarylates with number-average molecular weight and polydispersity index in the range of 30,100–35,300 and 1.82–2.17, respectively, exhibited high gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…DSC curves of polyesters MAPES-1, MAPES-2 and MAPES-3 showed T g at 142°C, 166°C and 154°C, respectively. A comparison of data with literature T g values of polyesters from BPA-TPC, (210°C) 45 BPA-IPC (181°C) 51 and BPA-TPC+IPC (195°C) 51 indicated that there is a drop in T g of (co)polyesters by the incorporation of packing-disruptive pendant maleimide groups connected via alkylene spacer. Copolyesters showed T g values in the range 162°C-178°C and the values tend to decrease with increase in mol % incorporation of BPA-MA.
Figure 4.DSC curves of (co)polyesters possessing pendant maleimide groups.
…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…DSC curves of polyesters MAPES-1, MAPES-2 and MAPES-3 showed T g at 142°C, 166°C and 154°C, respectively. A comparison of data with literature T g values of polyesters from BPA-TPC, (210°C) 45 BPA-IPC (181°C) 51 and BPA-TPC+IPC (195°C) 51 indicated that there is a drop in T g of (co)polyesters by the incorporation of packing-disruptive pendant maleimide groups connected via alkylene spacer. Copolyesters showed T g values in the range 162°C-178°C and the values tend to decrease with increase in mol % incorporation of BPA-MA.
Figure 4.DSC curves of (co)polyesters possessing pendant maleimide groups.
…”
Section: Resultsmentioning
confidence: 87%
“…On the other hand, homopolyesters derived from BPA and IPC or BPA and TPC are not soluble in the above mentioned organic solvents at room temperature as reported in the literature. 44,45 The improved solubility characteristics of BPA-MA-based homopolyesters could be attributed to the presence of pendant groups which interrupt the chain packing and increase the free volume, thus, allowing the penetration of solvent into the polymer matrix. So also, the pendant maleimide groups connected via alkylene spacer provide additional handle for interactions with solvent molecules.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the regular chain structure, the high melting temperature of polyarylates leads to poor processing fluidity 10 . Therefore, researchers usually use molecular structure design methods to improve these deficiencies, which mainly include the introduction of flexible spacer groups, 11–13 bulky pendant groups, 14–17 heterocyclic or nonlinear units, 18,19 copolymerization 20,21 and so on.…”
Section: Introductionmentioning
confidence: 99%